A multi-perspective review of the impact of a workplace relocation on commuting behaviour, commuting satisfaction and subjective well-being. Issue 3 (4th May 2023) - Maheshwari, Richa; Van Acker, Veronique; De Vos, Jonas; Witlox, Frank
ABSTRACT: Recently, a growing body of literature has focused on the role of daily mobility on subjective well-being (SWB). What is less well understood is the temporal effect of commuting on SWB/life satisfaction. To date, most studies addressing this temporal effect consider the impact of a residential relocation and not many studies reflect on the impact of a workplace relocation (WPR) on commuting behaviour, commuting satisfaction and SWB. This is surprising considering that changes at the destination of a commuting trip (i.e. relocation of the workplace) could be as important as changes at the origin of a commuting trip (i.e. relocation of the place of residence). This paper, therefore, aims to provide a systematic review of the impact of a WPR on commuting behaviour, commuting satisfaction and SWB. Using the PRISMA method, we identified 35 papers and developed a conceptual model summarising the main relationships between workplace relocation, commuting behaviour, commuting satisfaction and SWB. This conceptual model also reflects four disciplinary perspectives dominating research on the impacts of a workplace relocation.